MANAJEMEN FULL DAY SCHOOL: ANTARA PENINGKATAN KUALITAS BELAJAR DAN TANTANGAN PENGELOLAAN WAK-TU DI SMKN 1 SUNGAI PENUH - Yenti, Filda Lisma; Pohan, Muhammad Munawir (STKIP Pesisir Selatan, 2025)
This study aims to analyze the implementation of Full Day School (FDS) management at SMKN 1 Sungai Penuh and its impact on improving the quality of learning and character building of students. This study uses a qualitative approach with descriptive methods. Data were collected through observation, interviews, and documentation of the principal, curriculum vice principal, teachers, and students. The results of the study indicate that the implementation of FDS at SMKN 1 Sungai Penuh is based on the policy of the Jambi Provincial Education Office and the results of the Principals' Working Meeting (MKKS). This program has a positive impact on discipline, religiosity, and improving student learning outcomes, although still faced with challenges such as physical fatigue and boredom in the last hours of learning. The school management's efforts in organizing schedules, organizing religious activities, and building collaboration with parents are important factors in maintaining the effectiveness of FDS implementation. This study concludes that the success of FDS is largely determined by the balance between academic and non-academic activities and attention to the physical and psychological well-being of students through good time management.